Pengetahuan dan Keterampilan Dalam Pengawasan Kualitas Air Kolam Nila: Pelatihan Bagi Petani Ikan Skala Kecil - Ilham Pamungkas, Akbar (The Community Engagement Journal, 2025)
This activity aims to enhance the knowledge and skills of small tilapia fish farmers in Koya Timur which independently monitoring pond water quality. Ten farmers participated in the training, which included the presentation of materials on water quality parameters as well as hands-on practice using simple measuring instruments such as pH meters, DO meters, water thermometers, and ammonia–nitrite test kits. The methods used included interactive lectures, equipment demonstrations, field practice, and pre–post tests to evaluate participants knowledge improvement. The results showed a significant increase in participants understanding and technical abilities related to water quality monitoring. Farmers who previously relied solely on visual observation were now able to conduct standardized measurements, record the results in logbooks, and determine corrective actions such as feed adjustments, increased aeration, or partial water replacement. In addition, field practice in the farmers’ ponds provided real-life experience that reinforced their understanding of actual tilapia aquaculture conditions in the Koya Timur area. This activity had a positive impact on increasing farmers’ capacity to maintain water quality stability and prevent fish mortality due to poor water conditions. The training is expected to contribute to sustainable improvement of tilapia fish production in the Muara Tami District and serve as a model for future capacity building programs that can be replicated among other farming groups in the Jayapura region. Keywords: water quality monitoring, fish farming